Chronic inflammation in psoriasis promotes visceral adiposity associated with noncalcified coronary burden over time - Sajja, Aparna (JCI Insight, 2020)
BACKGROUND: Psoriasis is a chronic inflammatory skin disease associated with increased obesity, noncalcified coronary artery burden (NCB), and incident myocardial infarction. Here, we sought to assess the relationship among inflammation, visceral adipose tissue (VAT), and NCB. Furthermore, we evaluated whether improvement in VAT would be associated with reduction in NCB over time in psoriasis. METHODS: Consecutive psoriasis patients underwent coronary CT angiography to quantify NCB and abdominal CT to calculate VAT at baseline (n = 237), 1 year (n = 176), and 4 years (n = 50). RESULTS: Patients with high levels of high-sensitivity C-reactive protein (hs-CRP) had significantly greater visceral adiposity (17,952.9 ± 849.2 cc(3) vs. 13370.7 ± 806.8 cc(3), P < 0.001) and noncalcified coronary burden (1.26 ± 0.03 vs. 1.07 ± 0.02 mm(2)) than those with low levels of hs-CRP. Those with higher levels of VAT had more systemic inflammation (hs-CRP, median [IQR], 2.5 mg/L [1.0–5.3 mg/L] vs. 1.2 mg/L [0.6–2.9 mg/L]), with approximately 50% higher NCB (1.42 ± 0.6 mm(2) vs. 0.91 ± 0.2 mm(2), P < 0.001). VAT associated with NCB in fully adjusted models (β = 0.47, P < 0.001). At 1-year follow-up, patients who had worsening hs-CRP had an increase in VAT (14,748.7 ± 878.1 cc(3) to 15,158.7 ± 881.5 cc(3); P = 0.03), whereas those who had improved hs-CRP improved their VAT (16,876.1 ± 915.2 cc(3) to 16310.4 ± 889.6 cc(3); P = 0.04). At 1 year, there was 10.3% reduction in NCB in those who had decreased VAT (β = 0.26, P < 0.0001), which persisted in a subset of patients at 4 years (β = 0.39, P = 0.003). CONCLUSIONS: Inflammation drives development of VAT, increased cardiometabolic risk, and NCB in psoriasis. Reduction of inflammation associated with reduction in VAT and associated with longitudinal improvement in NCB. These findings demonstrate the important role of inflammation in the development of VAT in humans and its effect on early atherogenesis. TRIAL REGISTRATION: ClinicalTrials.gov NCT01778569. FUNDING: This study was supported by the National Heart, Lung, and Blood Institute Intramural Research Program (HL006193-05), the NIH Medical Research Scholars Program, a public-private partnership supported jointly by the NIH and contributions to the Foundation for the NIH from the Doris Duke Charitable Foundation (no. 2014194), the American Association for Dental Research, the Colgate-Palmolive Company, Genentech, and Elsevier as well as private donors.